Nilai Historis-Sosiologis Bendera Macan Ali dan Dunia Mistik Masyarakat Cirebon (Memaknai Ulang Konsep Islam Kejawen) - Afifi Hasbunallah (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2019)
AbstractSyncretism is a central issue for understanding the concept of Kejawen Islam. The intended syncretism is syncretism that appears independently as part of discursive differences originating from the same religion and culture. Syncretism in Kejawen Islam is a form of penetration of Islam as the dominant culture into the Kejawen culture which combines Hindu-Buddhist concepts which tend toward mystics. This can be seen in the Macan Ali flag which uses the tiger as a symbol of the greatness of the Cirebon Sultanate. This believe is living because tiger is a sacred mystical animal which existed before Islam entered Java, and still believed to this day.Keywords: Syncretism, Mysticism, Islam Kejawen, Macan Ali, Cirebon